THE EVALUATION OF TANK CARS DYNAMIC CHARACTERISTICS WITH DIFFERENT LEVELS OF UNDER FILLING - Kovtun, Ye. M.; Malyi, V. V.; Markova, O. M. (Science and Transport Progress, 2008)
Motion of a train composed of tank cars with various tank incomplete filling level is considered. The analysis of results obtained has shown that if there are tank cars with high incomplete filling in the train, the permissible speed of motion is reduced essentially.